Utilization of immediate postpartum intrauterine device and its associated factors among women who gave birth in public hospitals in West Wollega Zone, Oromia, Ethiopia - Guye, Ararso Hordofa; Kanea, Efa Bayissa; Nigussie, Tadesse; Girma, Derara; Shambi, Dame Banti (Frontiers in Medicine, 2023)
Background The utilization of an immediate postpartum intrauterine device (IPPIUD) during the postpartum period helps women to realize their desire for birth spacing and prevent unplanned pregnancies. However, many postpartum mothers do not undergo immediate postpartum family planning in developing countries, including Ethiopia, which consequently increases the risk of unplanned pregnancies and pregnancy-related complications. Objective To assess the utilization of an IPPIUD and its associated factors among women who gave birth in public hospitals in the West Wollega Zone in 2022. Methods An institutional-based cross-sectional study was conducted among 605 postpartum mothers who delivered their baby between 15 April and 15 May 2022 at public hospitals in the West Wollega Zone, Ethiopia. A systematic random sampling technique was used to select study subjects, and the data were collected using an interviewer-administered structured questionnaire, which was then entered into EpiData Entry version 4.6 and exported to the Statistical Package for Social Science version 26 for analysis. The variable with a p-value of ≤ 0.05 with an adjusted odds ratio and 95% confidence intervals was used to declare statistically significant association. Result The prevalence of the utilization of the IPPIUD among respondents who gave birth in West Wollega public hospitals within 48 h was 27.2% (95% CI, 23.7–30.9). Age ranging between 25 and 34 years (AOR = 4.27, 95%CI:1.68–10.85), early initiation of antenatal care (ANC; AOR = 1.91, 95%CI: 2.8–10.01), adequate knowledge of IPPIUD (AOR = 4.71, 95%CI: 2.63–6.63), favorable attitude toward family planning (AOR = 3.35, 95%CI: 2.07–5.44), planning of pregnancy (AOR = 2.21, 95%CI: 1.37–4.11), and counseling (AOR = 4.14, 95%CI: 2.60–6.68) were factors that were significantly associated with the utilization of IPPIUD. Conclusion According to the 2019 Ethiopia Mini Demographic and Health Survey (mini EDHS 2019), the utilization of an immediate postpartum intrauterine device was low, that is, 35%. Age of respondents, early initiation of antenatal care, favorable attitude toward, planning of pregnancy, adequate knowledge of, and counseling on IPPIUD utilization were significantly associated with the mother’s utilization of immediate postpartum intrauterine device. Thus, the zonal health office and health professionals should work toward encouraging all the women who gave birth at public hospitals to the utilization of immediate postpartum intrauterine devices by improving awareness among the women in that specific zone through counseling to increase the uptake of IPPIUD.